Dear Sergey,
I try to build it like this and it works. However, it looks clumsy.
Y[0] = pow(X[0],1)*log(p(X[0],a,b,var,r0)); Y[1] = pow(X[1],1)*log(p(X[1],a,b,var,r0)); Y[2] = pow(X[2],1)*log(p(X[2],a,b,var,r0)); Y[3] = pow(X[3],1)*log(p(X[3],a,b,var,r0)); Y[4] = pow(X[4],1)*log(p(X[4],a,b,var,r0)); Y[5] = pow(X[5],1)*log(p(X[5],a,b,var,r0)); Y[6] = pow(X[6],1)*log(p(X[6],a,b,var,r0)); Y[7] = pow(X[7],1)*log(p(X[7],a,b,var,r0)); Y[8] = pow(X[8],1)*log(p(X[8],a,b,var,r0)); Y[9] = pow(X[9],1)*log(p(X[9],a,b,var,r0));
Is there a better was=y to handle this?
Cheers, Van
